Metode Sugestopedia dan Implikasinya dalam Pembelajaran Bahasa Arab Keterampilan Mengarang (Insyā’) - Fakturmen Fakturmen (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2020)
One of the innovative learning methods today is the Suggestopedia method. This article aims to examine the theory of suggestopedia and its implications in learning Arabic writing skills (insyā’). The research method of this article uses a literature review. Sources of data obtained from the exploration of literature related literature studies. Data is examined critically and deeply through data triangulation. The results of the analysis of this article are that the suggestopedia method has implications in learning Arabic writing skills (insyā’) on several aspects, including aspects of learning objectives, aspects of learning techniques, aspects of learning strategies, aspects of instructional media, aspects of the learning environment, and aspects of learning levels.